The Effect of Product Quality, Promotion, and Design on the Purchase Decision of Fipper Brand Footwear Products in Surabaya - Saddam, Muhammad; Noor, Asmirin; Kuswandi, Kuswandi (Journal of Management and Administration Provision, 2025)
The purpose of this study was to determine the effect of product quality, promotion, and design on purchasing decisions for Fipper brand footwear products in Surabaya, both individually and simultaneously. In addition, this study also attempted to identify the factors that most influence purchasing decisions for Fipper footwear products. The independent variables used are Product Quality (X1), Promotion (X2), and Design (X3), while the dependent variable is Purchase Decision (Y). In this study, the sample taken was 100 people in Surabaya who use Fipper brand footwear products using random sampling techniques. Data collection was carried out by indirect observation and distributing questionnaires to Fipper product users in Surabaya. This study uses Multiple Linear Regression Analysis based on SPSS software. From the results of the T-Test analysis, it is known that product quality (X1) and promotion (X2) do not have a significant effect on purchasing decisions for Fipper footwear products in Surabaya. On the other hand, the design variable (X3) has a significant effect on purchasing decisions, so that design is the main factor influencing consumer decisions. In addition, an R² value of 0.585 or 58.5% was obtained. This means that product quality, promotion, and design together have a positive influence on purchasing decisions for Fipper brand footwear products.